Women and the capital market: study on the profile of brazilian female investors - Vieira, Flávia Mônaco; Pires, Vanessa Martins; Schneider, Luis Carlos; Wiedenhöft, Guilherme Costa (Revista de administração da UFSM, 2025)
Purpose: The growing participation of women in the Brazilian capital market contrasts with the limited knowledge about the profile of these investors. To fill this gap, this study aims to understand the profile of Brazilian female investors, analyzing factors that influence their investment decisions, such as education, age, social class, family background and geographic region. Methodology: To test the research hypotheses, a quantitative approach was used with the aid of the Sider® tool and libraries in Python, NumPy for numerical operations, SciPy for statistical tests such as Chi-square, Statsmodels for advanced analysis and Matplotlib/Seaborn for data visualization. Clustering techniques with the K-Means algorithm were applied to identify the profiles of the investors, based on sociodemographic factors. Findings: Factors such as education, economic class and family background significantly influence investment intention. Although most investors have a conservative profile, focused on low-risk assets, investors with higher income and education tend to diversify their portfolios, including more sophisticated assets. Three investor profiles were identified: experienced and financially stable (Cluster 1), young investors seeking to build wealth (Cluster 2) and young investors just starting out on their financial journeys (Cluster 3). Originality: The research contributes to the literature on personal finance by understanding the profile of Brazilian female investors based on sociodemographic factors, given the low density of studies on this subject. The results of the research allow for various applications, supporting the creation of public policies on financial education and aimed at building a more inclusive capital market.